Examining Critical Effects of Service Quality Attributes on Clients’ Repurchase Intension Through Clients’ Satisfaction: An Empirical Investigation on SERVQUAL Model. - Isra Firmansyah, Fahmi Ichwansyah, Hermansyah M. Hasan (International Journal of Advanced Science and Technology, 2020)
There are many insurance providers in Indonesia offer different allure package to their clients. Despite having the right set of policies between insurance providers and clients, there are numerous complaints from clients regarding the service quality assured by providers. In addition to this, there are immense number of research in the area of service quality, however, there is a significant lacuna in the context of insurance service providers. therefore, this study is one of the very few that conduct an empirical investigation to identify the effect of service quality on customers’ satisfaction and its mediating effect on repurchase intention, in the health insurance context. A conceptual model was developed based on extensive literature review and the theory of SERVQUAL. A web-based structure questionnaire was developed based on several important steps and obtained more than 190 responses from the five most prominent insurance companies in Indonesia. Multiple regression and Sobel test were applied to measure direct and mediating effect respectively. Results explicitly indicated that all five service attributes are important for customer satisfaction in the context of health insurance. Similarly, Sobel test confirmed the mediating effect of customer satisfaction on repurchase intention. Indeed this study provides a new perspective of service characteristics for the insurance industry, for instance, results indicated that empathy, in others words understanding clients is of the most important service characteristics that can significantly influence clients satisfaction.  Moreover, this study provides several insightful strategies that can be helpful to the insurance industry, especially in Indonesia.